Development, Pre-Testing and Feasibility Testing of Multi-Component Interventions, Critical for Mental Health Promotion in Primary Care among Mexican-American Adolescents Living in Rural America - Jane Dimmitt Champion (MDPI AG, 2023)
Rural America is often viewed as bereft of social problems facing urban America. Rural families, however, experience stressors due to low employment rates, fewer educational opportunities, a relatively increased incidence of poverty and limited access to mental health care. These families are at increased risk for substance use, violence and associated psychological distress that occurs when failing to cope with stress. Rural children, experiencing these stressors and affected by barriers of culture, poverty and remote access to mental health care, are at higher risk for these negative health outcomes. The need for culturally appropriate intervention tailored to the target population, rural Mexican-American adolescent women, is consistently supported by evidence. A one-size-fits-all approach most likely will not effectively impact behavior and health outcomes. The fact that few studies evaluated effects of mental health interventions on multiple outcomes including substance use, violence, unintended pregnancy and STI is problematic given previously noted associations. Evidence is needed to evaluate associations between mental health interventions and these outcomes. This manuscript presents results of preliminary studies, conducted using a multi-method research approach for development, pre-testing and feasibility testing of interventions for rural primary care settings. This methodology is appropriate when dealing with the complexity of social phenomena. It provides a look at an issue from all angles and thereby the cultural context and perspective informing intervention development. These multi-component interventions are critical for mental health promotion among Mexican-American adolescent women living in rural America.